2005
DOI: 10.1002/tox.20145
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of histopathological and cytogenetic effects onLepomis gibbosus (Pisces: Perciformes) in the Çine stream (Aydın/Turkey) with determination of water pollution

Abstract: Water quality and the distribution of some heavy metals in three different organs of Lepomis gibbosus from the Cine Stream were studied. Also, histopathological changes in gill, liver, and muscle tissue were examined at light microscopical level. Micronucleus (MN) formation in fish erytrocytes, as an indicator of chromosomal damage, has been increasingly used to detect the genotoxic potential of environmental contaminants. The frequency of MN was examined from samples of fish from the Cine Stream and a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 72 publications
(72 reference statements)
5
38
0
3
Order By: Relevance
“…Micronuclei and binuclei frequencies were significantly elevated in fish exposed to water from polluted areas. In a study by Koca et al (2005) to determine genetic damage in Lepomis gibbosus in the Çine stream (Aydın/Turkey), it was reported that genetic damage existed by examining MN in fish erythrocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Micronuclei and binuclei frequencies were significantly elevated in fish exposed to water from polluted areas. In a study by Koca et al (2005) to determine genetic damage in Lepomis gibbosus in the Çine stream (Aydın/Turkey), it was reported that genetic damage existed by examining MN in fish erythrocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Studies related to the bioaccumulation of metals in tissues demonstrated the variation of metal accumulations (Watanabe et al, 2003, Masoud et al, 2007and Younis et al, 2015. Moreover, Koca et al (2005) postulated that the accumulation patterns of contaminants in fish and other aquatic organisms depend on both uptake and elimination rates of contaminants. Bioaccumulation of metals may lead to high mortality rate or cause many biochemical and histological alterations in the survived fish (Rashed, 2001a;Rashed, 2001b andSoltan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that O. niloticus have a selective maintenance of metals in their tissues. Koca et al (2005) reported that the bioaccumulation patterns of a certain pollutant in the aquatic biota depend mainly on the uptake and removal rates of this pollutant. Bioavailability of the studied metals was observed to be tissue specific with different accumulation patterns.…”
Section: Bioaccumulation Of Metals In the Key Body Tissuesmentioning
confidence: 99%